2009
DOI: 10.1517/17425240903158909
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic peptides for cancer therapy. Part II – cell cycle inhibitory peptides and apoptosis-inducing peptides

Abstract: Inhibition of cancer cell proliferation directly using peptides that arrest the cell cycle or induce apoptosis is a promising strategy. Peptides can be designed that interact very specifically with cyclins and/or cyclin-dependent kinases and with members of apoptotic cascades. Use of these peptides is not limited by their design, as a rational approach to peptide design is much less challenging than the design of small molecule inhibitors of specific protein-protein interactions. However, the limitations of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 97 publications
0
39
0
2
Order By: Relevance
“…14 The competitive inhibitors are able to mask an interaction domain and make this domain inaccessible for the natural interaction partner which in turn is required for proper function and finally for the implementation of a particular cellular phenotype. 15,16 In a next step, these peptide ligand interactions with crucial domains of target proteins can be further exploited in high throughput screening systems to find low molecular weight compounds which act as functionally equivalent analogs.…”
Section: Inhibition Of Stat3 and Survivin Through Peptide Ligandsmentioning
confidence: 99%
“…14 The competitive inhibitors are able to mask an interaction domain and make this domain inaccessible for the natural interaction partner which in turn is required for proper function and finally for the implementation of a particular cellular phenotype. 15,16 In a next step, these peptide ligand interactions with crucial domains of target proteins can be further exploited in high throughput screening systems to find low molecular weight compounds which act as functionally equivalent analogs.…”
Section: Inhibition Of Stat3 and Survivin Through Peptide Ligandsmentioning
confidence: 99%
“…A major concern in therapeutic development is therefore drug delivery. For these reasons, effort has been put into developing efficient delivery strategies including nano-particle-, polycationic-and lipid-based methods [11]. However, only a few of them have reached clinical trials [9].…”
Section: Therapeutic Peptide Design Improvementmentioning
confidence: 99%
“…Finally, they can be produced easily and at low cost. All these advantages have made the anti-cancer peptide research field very active lately as reported in a number of interesting recent reviews [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of these CDK inhibitor proteins can be appreciated by the observation that inactivation of INK4a is one of the most frequent genetic traits in tumorigenesis. Whilst therapy with peptides show great promise, there are technical problems pertaining to the delivery of these synthetic peptides, and so far most of the experiments conducted have been carried out with cell lines [22].…”
Section: Cell Cycle and Cyclin-dependent Kinasesmentioning
confidence: 99%